Butylated Hydroxytoluene Improves Lignin Removal by Organosolv Pretreatment of Sugarcane Bagasse - Schmatz, Alison Andrei [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2022)
Advantages in biomass pretreatment could be reached by improving lignin removal. In this study, the antioxidant butylated hydroxytoluene (BHT) was evaluated for lignin removal from biomass. In pretreatments performed at 121 °C with 50% (v/v) ethanol as solvent, the presence of BHT resulted in 45.28% and 72.45% lignin and hemicellulose removal, against its absence that resulted in 35.09% and 56.31%, respectively. The use of BHT in lignin removal under these conditions represents an improvement in the pretreatment reducing the biomass recalcitrance. FTIR analyses showed that organosolv pretreatment with BHT influenced band intensity of the pseudo-lignin, while in acid medium similarity was observed among the spectra. The enzymatic hydrolysis of pretreated biomass suffered the influence of hemicellulose and lignin removal. Pretreatments at 121 °C resulted in the highest cellulose conversion with 75% ethanol (58.67%), while pretreated biomass at 160 °C with 0.3% BHT resulted in a 59.04% of glucose yield. The use of BHT increased the lignin solubilization from the biomass in the organosolv pretreatment, increasing the effectiveness of the process, collaboration for further use of lignin.
Keywords: Bioethanol; Fermentation; Glucose; Lignocellulosic biomass; Low-cost antioxidant